Feasibility study of subject‐specific, brain specific‐absorption‐rate maps retrieved from MRI data - Martinez, Jessica A.; Zanovello, Umberto; Arduino, Alessandro; Hu, Houchun Harry; Moulin, Kevin; Ogier, Stephen E.; Bottauscio, Oriano; Zilberti, Luca; Keenan, Kathryn E. (Magnetic resonance in medicine, 2025)
Introduction Specific absorption rate (SAR) is crucial for monitoring radiofrequency power absorption during MRI. Although local SAR distribution is usually calculated through numerical simulations, they are impractical during exams, limiting real‐time patient‐specific SAR assessment. This study confirms the feasibility of deriving in vivo, subject‐specific, image‐based SAR and 10‐g SAR maps directly from MRI data. Methods Complex B1+ maps were derived by combining a B1+ product (XFL) magnitude sequence with balanced steady‐state free precession phase. Anatomical information and tissue masking were obtained from a T1 magnetization‐prepared rapid gradient echo sequence. Electrical conductivity maps were generated from balanced steady‐state free precession phase. Whole‐brain SAR maps were created from MRI data acquired at 3 T using a 32‐channel head coil on 2 healthy volunteers. A correction factor was applied to account for underestimation due to reliance on measurable B1+ data. Numerical simulations compared image‐based SAR with simulation‐based SAR distributions. Results A multi‐slice image‐based brain SAR map was obtained in 12 min (9‐min acquisition, 3‐min SAR reconstruction). In vitro experiments validated B1+ distribution and electrical conductivity values. Calculated electrical conductivities for in vitro and in vivo experiments were within reference ranges. Image‐based SAR and 10‐g SAR maps showed a distribution similar to simulation‐based maps (r = 0.5) after correction. Conclusions This study shows the feasibility of inline, subject‐specific SAR and 10‐g SAR maps from standard brain clinical sequences. Image‐based SAR maps can be a practical alternative during MRI exams when simulations are not feasible.